Characterisation of the faecal metabolome and microbiome of Thoroughbred racehorses. (29th September 2014) - Proudman, C. J.; Hunter, J. O.; Darby, A. C.; Escalona, E. E.; Batty, C.; Turner, C.
Summary Reasons for performing study The intestinal bacterial community of the horse is a key determinant of intestinal and whole body health. Understanding the bacterial community structure and function is an important foundation for studies of intestinal health and disease. Objectives To describe the faecal bacterial community and volatile organic compounds (VOCs) of the faecal metabolome of healthy Thoroughbred racehorses and to characterise responses to dietary supplementation with amylase‐rich malt extract. Study design Intervention study. Methods Faecal samples were collected noninvasively before and 6 weeks after supplementation in 8 privately owned Thoroughbred racehorses in active race training. Faecal metabolome was characterised using thermal desorption‐gas chromatography‐mass spectrometry (TD‐GC‐MS), with spectral analysis performed using AMDIS and compared against the NIST database. Taxonomic description of the faecal microbiota was achieved using error‐corrected 454 pyrosequencing data from 16S rRNA gene amplicons. Results The faecal metabolome of our study population was dominated by organic acids, alcohols and ketones. We identified 81 different VOCs only 28 of which were present in >50% of samples indicating functional diversity. Faecal VOC profiles differed between first and second sampling point, some VOCs being significantly reduced post supplementation, consistent with a marked response to dietary amylase‐rich malt extract. Faecal microbiota was characterised as highly diverse; samples demonstrated verifiable diversity in the range 1200–3000 operational taxonomic units (OTUs) per individual. The methods used also describe high levels of infrequent, low abundance OTUs. Faecal microbial community structure was found to be different following dietary supplementation. Differences in several low abundance bacterial taxa were detected and also some evidence of interhorse variation in response. Conclusions The volatile faecal metabolome of Thoroughbred racehorses is dominated by organic acids, alcohols and ketones; this study demonstrates that dietary supplementation with amylase‐rich malt extract may significantly alter the profile of VOCs. The faecal microbiome is highly diverse, dominated by Firmicutes and Bacteroidetes. Small but significant changes in microbial community structure were detected following dietary supplementation. This study describes the faecal metabolome and microbiome of healthy Thoroughbred racehorses against which future studies of disease and dietary intervention can be benchmarked.